2005
DOI: 10.1016/j.ympev.2005.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and comparative biogeography of Pionopsitta parrots and Pteroglossus toucans

Abstract: Studies of Neotropical birds, and their distributions and areas of endemism, in particular, have been central in the formulation of hypotheses proposed to explain the high species diversity in the Neotropics. We used mtDNA sequence data (ATPase 6 and 8, COI, and cyt b) to reconstruct the species-level phylogenies for two genera, Pionopsitta (Aves: Psittacidae) and Pteroglossus (Aves: Ramphastidae), compare our results with previous morphology-based phylogenetic analyses, and estimate the absolute timing of lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 58 publications
5
44
0
6
Order By: Relevance
“…First, these works and some others (e.g., CRACRAFT & PRUM 1988, AMORIM & PIRES 1996, BATES et al 1998, RON 2000, EBERHARD & BERMINGHAM 2005) have pointed to a common origin for most of the biota in the Atlantic Rain Forest, and its close relationship with the Amazon forest biota. Furthermore, the region where Hernandariinae lives, from Org to SC was secondarily separated from northern areas (AMORIM & PIRES 1996, PINTO-DA-ROCHA et al 2005, YAMAGUTI & PINTO-DA-ROCHA 2009.…”
Section: Geographical Distribution (Figs 185-189)mentioning
confidence: 95%
“…First, these works and some others (e.g., CRACRAFT & PRUM 1988, AMORIM & PIRES 1996, BATES et al 1998, RON 2000, EBERHARD & BERMINGHAM 2005) have pointed to a common origin for most of the biota in the Atlantic Rain Forest, and its close relationship with the Amazon forest biota. Furthermore, the region where Hernandariinae lives, from Org to SC was secondarily separated from northern areas (AMORIM & PIRES 1996, PINTO-DA-ROCHA et al 2005, YAMAGUTI & PINTO-DA-ROCHA 2009.…”
Section: Geographical Distribution (Figs 185-189)mentioning
confidence: 95%
“…However, a calibration for cyt b was assumed based on a molecular rate of 2.1% (see Weir & Schluter 2008). This rate has been used in parrots (Groombridge et al 2004;Eberhard & Bermingham 2005;Tavares et al 2006;Ribas & Miyaki 2007;Ribas et al 2009) and other birds for a period of c. 12 million years (Shields & Wilson 1987;Tarr & Fleischer 1993;Fleischer et al 1998;Weir & Schluter 2008).…”
Section: Molecular Clockmentioning
confidence: 99%
“…The genus Pteroglossus (Ramphastidae) Molecular data published for the Amazonian Pteroglossus viridis/inscriptus and Pteroglossus bitorquatus/flavirostris species complexes showed that these two groups have distinct evolutionary histories (Eberhard and Bermingham 2005). In the former group, the first split occurred between eastern Brazilian and Amazonian populations, followed by the separation between Guianan shield (P. viridis) and southern Amazonian populations (estimated as being completed by 1.5 Ma); the subsequent split involved Brazilian shield (P. inscriptus) and western Amazonian populations (P. I. humboldti) and is thought to have been completed by 1 Ma (Fig.…”
Section: Amazonian Geology Revisited: Implications For Avian Historicmentioning
confidence: 99%